Sítio Alto : entre dança, história e etnicidade - Silva, Daniela Santos (2017)
The present work has as analytical focus the process of recognition of the Sítio Alto community as a remaining quilombola. The goal is to develop an analysis of how the community in question has built its ethnic identity through memory and wheel dancing. In this sense, I try to understand how the ethnic issue has been diffused and socially constructed among the residents of Sítio Alto in the last five years. In this same scenario, the community's trajectory and its struggle for the recognition and certification of the territory as remaining quilombola are questioned, truz endowed with rights in relation to the public policies undertaken by the State in this category.